The guy she was interested in wasn't a guy at all. 1 - Arai, Sumiko (Yen Press, 2024)
Fashionable and upbeat high schooler Aya loves listening to rock, but no one else seems to share her interest...until she meets a cool, stylish employee at a CD shop. Dressed in black from head to toe, he has this air of mystery about him, and his taste in music is impeccable. Aya falls hard for him--not knowing her crush is actually her female classmate Mitsuki! For her part, Mitsuki generally keeps to herself and avoids standing out at school. But given that she sits right next to Aya, Mitsuki's all too aware of the other girl's feelings, and she's afraid to reveal the truth. So why does she find herself talking with Aya more and more...?